The teenage coeliac: follow up study of 102 patients. Issue 8 (August 1988) - Kumar, P J; Walker-Smith, J; Milla, P; Harris, G; Colyer, J; Halliday, R
Abstract : Over a 10 year period a total of 102 teenage patients with coeliac disease were assessed on transfer from paediatric hospitals to an adult clinic. Fifty seven patients said they were on a strict gluten free diet; 36 were semistrict, and nine admitted to eating a normal diet. Jejunal mucosal abnormalities, however, suggested that many patients on the 'strict' diet were actually consuming gluten. All patients were well with biochemical parameters within the normal range. Height percentiles were not significantly different from the normal population but patients, as a group, were significantly lighter.